Entre uma língua e outra: desdobramentos das designações língua materna e língua estrangeira no discurso do sujeito pesquisador da linguagem - Rosa, Marluza Terezinha da (2009)
Throughout this study, we aim at pondering over the notion of language, by questioning delimitations usually established between Mother Tongue and Foreign Language in order to investigate meaning effects produced by these designations as well as by their (re)formulations. For be able to reflect upon the problematic related to the designations from the bias of Discourse Analysis, we focus on the discourse produced by the subject researcher on language, who experiences a situation concerning more than two languages and cultures. Thus, we are involved in an approaching of the discursive functioning allied to the production of linguistic knowledge, by dealing with the movement of saying in an academic-scientific ambit. Our hypothesis is that the ways of referring to language put in process by this subject could be a result of its identification with the languages among which it is in motion. In this way, we focus on the functioning of discourse from this subject position, which is marked by the movement among languages, with the purpose of observing which meaning effects are produced in a discourse about the language that signifies by the manners it is designed.